Efeito da aplicação ativa dos ácidos fluorídrico e fosfórico na resistência de união de um cimento resinoso à cerâmica feldspática e à vitrocerâmica - Nascimento, Bruna Luiza do (2018)
The objective of this study was to evaluate the effect of the active application of hydrofluoric and phosphoric acids by the use of sonic vibration apparatus on the bond strength of a resin cement to a feldspathic and a glass ceramic for CAD/CAM. Ceramic blocks (Mark II and Suprinity) were cut and distributed in 2 groups according to the material used. Each group was subdivided into 6 subgroups according to the treatment technique (n=12): F - manufacturer's recommended technique (control); AF - equal to control, but with active application of hydrofluoric acid; F+P - equal to control, with cleaning with 37% phosphoric acid; AF+P - equal to F+P, with active application only of hydrofluoric acid; F+AP - equal to F+P with active application only of phosphoric acid; AF+AP - equal to F+P with active application of both acids. After that, cylinders (1 mm in diameter and 1 mm in height) were made with resin cement. The specimens were stored in distilled water at 37°C for 24 hours. Afterwards, they were submitted to the mechanical test of micro-shear in a universal test machine (Emic) with a velocity of 0.5 mm/min. The bond strength data (MPa) were submitted to analysis of variance and Tukey's test, with a significance level of 5%. There was a significant difference between the groups for both ceramics (Mark II - p<0.0001; Suprinity - p<0.0001). The feldspathic ceramics (Mark II) showed the following results (MPa): F 29.66; AF 24.06; F+P 24.00; AF+P 32.11; F+AP 30.79; AF+AP 41.75.A glass ceramic (Suprinity) presented the following results (MPa): F 34.91; AF 20.32; F+P 27.11; AF+P 38.77; F+AP 24.27; AF+AP 31.04. For feldspathic ceramics the best results were observed when the active application of the hydrofluoric acid associated with the application of phosphoric acid (with active or passive application). For the glass ceramic, the behavior of the groups was similar, regardless of the treatments performed on the ceramic surface prior to cementation. It can be concluded that the different treatments of the surface of the ceramic before the cementation interfered significantly in the bond strength of the ceramics to the resin cement, depending on the type of ceramic.